Prognostic factors associated with development of infected necrosis in patients with acute necrotizing or severe pancreatitis—A systematic review and meta-analysis. Issue 5 (20th May 2022) - Tran, Alexandre; Fernando, Shannon M.; Rochwerg, Bram; Inaba, Kenji; Bertens, Kimberly A.; Engels, Paul T.; Balaa, Fady K.; Kubelik, Dalibor; Matar, Maher; Lenet, Tori I.; Martel, Guillaume
Abstract : This meta-analysis confirms the association between several clinical early prognostic factors and the risk of IPN development among patients with severe or necrotizing pancreatitis. Abstract : PURPOSE: Acute pancreatitis is a potentially life-threatening condition with a wide spectrum of clinical presentation and illness severity. An infection of pancreatic necrosis (IPN) results in a more than twofold increase in mortality risk as compared with patients with sterile necrosis. We sought to identify prognostic factors for the development of IPN among adult patients with severe or necrotizing pancreatitis. METHODS: We conducted this prognostic review in accordance with systematic review methodology guidelines. We searched six databases from inception through March 21, 2021. We included English language studies describing prognostic factors associated with the development of IPN. We pooled unadjusted odds ratio (uOR) and adjusted odds ratios (aOR) for prognostic factors using a random-effects model. We assessed risk of bias using the Quality in Prognosis Studies tool and certainty of evidence using the GRADE approach. RESULTS: We included 31 observational studies involving 5, 210 patients. Factors with moderate or higher certainty of association with increased IPN risk include older age (uOR, 2.19; 95% confidence interval [CI], 1.39–3.45, moderate certainty), gallstone etiology (aOR, 2.35; 95% CI, 1.36–4.04, high certainty), greater than 50% necrosis of the pancreas (aOR, 3.61; 95% CI, 2.15–6.04, high certainty), delayed enteral nutrition (aOR, 2.09; 95% CI, 1.26–3.47, moderate certainty), multiple or persistent organ failure (aOR, 11.71; 95% CI, 4.97–27.56, high certainty), and invasive mechanical ventilation (uOR, 12.24; 95% CI, 2.28–65.67, high certainty). CONCLUSION: This meta-analysis confirms the association between several clinical early prognostic factors and the risk of IPN development among patients with severe or necrotizing pancreatitis. These findings provide the foundation for the development of an IPN risk stratification tool to guide more targeted clinical trials for prevention or early intervention strategies. LEVEL OF EVIDENCE: Systematic review and meta-analysis, Level IV.